The risk of stroke after acute myocardial infarction in patients with and without atrial fibrillation: A nationwide cohort study. Issue 12 (14th October 2021) - Chiang, Cheng-Hung; Hung, Wan-Ting; Huang, Wei-Chun; Jheng, Ying-Chun; Lai, Wei-Yi; Lin, Yi-Ying; Lin, Tzu-Wei; Lin, Kun-Chang; Cheng, Chin-Chang; Kuo, Feng-Yu
Abstract : Background: Acute myocardial infarction (AMI) and atrial fibrillation (AF) are risk factors for stroke. The risk of stroke after AMI may differ between patients with and without AF. The aim of this study was to evaluate the impact of AF on stroke in patients after the first AMI. Methods: This was a retrospective, nationwide cohort study. Patients with a primary diagnosis of a first AMI between 2000 and 2012 were included. All patients were followed up until ischemic stroke or transient ischemic attack (TIA), or December 31, 2012, whichever occurred first. Kaplan–Meier cumulative survival curves were constructed to compare ischemic stroke or TIA between AMI patients with and without AF. Results: A total of 170 472 patients were enrolled in this study. Among them, 8530 patients with AF were identified. The propensity score matching technique was used to match 8530 patients without AF of similar ages and sexes. Overall, the 12-year stroke rate was significantly higher in patients with AF than in those without AF (log-rank p < 0.001), including different sexes, ages, and interventional therapy subgroups. Patients with pre-existing AF had higher stroke rates than those with newly diagnosed AF in male sex, age below 65 years, and those receiving interventional therapy subgroups. In Cox proportional-hazard regression analysis, AF was an independent risk factor for stroke after the first AMI (hazard ratio, 1.67; 95% CI: 1.5-1.87). Conclusion: AF significantly increases stroke risk after the first AMI. In patients with AF, those with pre-existing AF have higher stroke risks in male sex, age below 65 years, and those with interventional therapy than those with newly diagnosed AF.